The Influence of Transformational Leadership Style and Work Environment on the Performance of Bangka Belitung Islands Regional Police Employees - Tri Farina; Rini Pajlia; Juhari Juhari (TechTalent & Business Review, 2026)
This study aims to analyze and empirically test the influence of transformational leadership style and work environment on the performance of Bangka Belitung Islands Regional Police employees. Employee performance is a strategic factor in supporting the effectiveness of police duties and improving the quality of public services. This study uses a quantitative approach with a causal associative method. The research data was obtained by distributing questionnaires to 150 employees of the Bangka Belitung Islands Regional Police, who were selected using probability sampling with the simple random sampling method. The research instruments were tested for validity and reliability, and all statement items were declared valid and reliable. The data analysis technique used was multiple linear regression analysis with the help of statistical software, preceded by classical assumption testing. The results showed that transformational leadership style had a positive and significant effect on employee performance, as evidenced by a significance value of 0.000 < 0.05.  The work environment has also been proven to have a positive and significant effect on employee performance with a significance value of 0.000 < 0.05. Furthermore, the simultaneous test results show that transformational leadership style and work environment together have a positive and significant effect on employee performance. The coefficient of determination (R²) value of 0.523 indicates that 52.3% of employee performance variation can be explained by transformational leadership style and work environment, while the rest is influenced by other variables outside the research model. These findings indicate that the application of effective transformational leadership style, accompanied by the creation of a conducive work environment, can increase employee motivation, commitment, and productivity. This study provides a theoretical contribution to the development of human resource management studies in the public sector, particularly in police institutions, and provides practical implications for the leadership of the Bangka Belitung Islands Regional Police in formulating leadership development and work environment improvement policies to improve employee performance in a sustainable manner.